WORD-COMBINATIONS AND THEIR TYPES (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article offers an insightful exploration of word combinations and their multifaceted types within language. It delineates the various categories of word combinations, encompassing phrases, idioms, collocations, compound words, and proverbs, providing a comprehensive understanding of each type's structure and function.The piece delves into the significance of comprehending these word combinations, emphasizing their pivotal role in fostering communication clarity, enhancing fluency, and enabling effective expression of thoughts and emotions. It elucidates how familiarity with these linguistic constructs contributes to cultural understanding, reflecting values and traditions inherent in language.